2019
DOI: 10.1094/pdis-08-18-1387-re
|View full text |Cite
|
Sign up to set email alerts
|

Treatment With Wheat Root Exudates and Soil Microorganisms From Wheat/Watermelon Companion Cropping Can Induce Watermelon Disease Resistance Against Fusarium oxysporum f. sp. niveum

Abstract: Companion cropping with wheat (Triticum aestivum L.) can enhance watermelon [Citrullus lanatus (Thunb.) Matsum. & Nakai] wilt disease resistance against Fusarium oxysporum f. sp. niveum. However, the mechanism of resistance induction remains unknown. In this study, the effects of microbial community dynamics and the interactions between wheat and watermelon plants, particularly the effect of wheat root exudates on watermelon resistance against F. oxysporum f. sp. niveum, were examined using a plant-soil fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 54 publications
(83 reference statements)
1
29
0
Order By: Relevance
“…At the same time, the genes in groups of Post translational; Intracellular tra cking, secretion and Cell motility and Cell wall: membrane envelope biogenesis had increased signi cantly in SA3. The results con rmed our hypos of rhizosphere microbiome assemblage is affected by SA signal (Chaparro et al, 2014;Delgado-Baquerizo et al, 2018;Mendes et al, 2011;Vorholt et al, 2017) and the 3dpi is a key time point for watermelon plants to activate disease resistance (Li et al, 2019;Ren et al, 2016;Xu et al, 2015). Notably, the resistance genes from Glycoside Hydrolases and Polysaccharide Lyases have highly accumulated in SA3, especially the result indicated that AAC6_IIC (drug class of aminoglycoside antibiotic, resistance mechanism of antibiotic inactivation) has a signi cant accumulation constantly after SA application compared with control group.…”
Section: Discussionsupporting
confidence: 66%
“…At the same time, the genes in groups of Post translational; Intracellular tra cking, secretion and Cell motility and Cell wall: membrane envelope biogenesis had increased signi cantly in SA3. The results con rmed our hypos of rhizosphere microbiome assemblage is affected by SA signal (Chaparro et al, 2014;Delgado-Baquerizo et al, 2018;Mendes et al, 2011;Vorholt et al, 2017) and the 3dpi is a key time point for watermelon plants to activate disease resistance (Li et al, 2019;Ren et al, 2016;Xu et al, 2015). Notably, the resistance genes from Glycoside Hydrolases and Polysaccharide Lyases have highly accumulated in SA3, especially the result indicated that AAC6_IIC (drug class of aminoglycoside antibiotic, resistance mechanism of antibiotic inactivation) has a signi cant accumulation constantly after SA application compared with control group.…”
Section: Discussionsupporting
confidence: 66%
“…Intercropping is at the heart of traditional Chinese agriculture [26], can improve ecological stability of farmland by improving nutrient absorption [27], reduce toxicity of allelopathic substances [14], improves microecological environment and control of soil-borne diseases [28]. Intercropping is considered an important model of sustainable agricultural development due its increased production, e cient use of resources and better control of disease [29].…”
Section: Effect Of Intercropping On Physiological and Biochemical Resmentioning
confidence: 99%
“…Recent work has demonstrated that intercropping and other diversi ed cultivation methods can enhance host plant resistance to pathogens, and control occurrence of soil-borne diseases. Mechanisms of host defense responses included; increased expression of defense-related genes in watermelon roots of a wheat/watermelon companion cropping system [19]; increased activity of defense enzymes in roots of tomato in a potato/tomato intercropping system [20]; improved defense enzyme activity in garlic leaves and increased garlic physiological resistance in an eggplant/garlic intercrop system [21]. To our knowledge, it is not known whether intercropping affects host resistance to FA stress, especially in wheat / faba bean intercrop systems, or how the defense response of faba bean changes.…”
Section: Introductionmentioning
confidence: 99%
“…Watermelon ( Citrullus lanatus ) Fusarium wilt disease caused by Fusarium oxysporum f. sp. niveum (FON) poses a serious threat to watermelon quality and yield [ 1 , 2 , 3 ]. Symptoms such as rotted, discolored roots and brown vascular bundles appeared in Fusarium wilt diseased plants [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different techniques include chemical control [ 5 ], biological control [ 6 , 7 ], grafting [ 8 ], and the use of disease-resistant cultivars [ 9 , 10 ] are utilized to overcome this disease. Many researchers found that different cultivation systems, such as intercropping [ 2 , 11 ], companion cropping [ 12 ], and rotated cropping [ 1 ], represent safe and efficient methods to control soil-borne diseases. Previously, researchers have focused on mutual recognition and recognition competition between the host plants, pathogens, pathogenic factors, and host plant defense factors.…”
Section: Introductionmentioning
confidence: 99%